Government size and economic growth: empirical study on organization of Islamic cooperation countries - Duasa, Jarita (RMP Publications, 2018)
The issue of a correct ‘government size’ for economic prosperity of a nation is highly linked with the issue of optimal ‘role of state’. The present study attempts to utilize more efficient econometric methods on a sample of Organisation of Islamic Cooperation (OIC) countries over a specific period of time in order to investigate relationship between government size and economic growth. It also attempts to identify optimal size of government (role of state) that maximize the economic growth of the countries by applying static and dynamic panel estimations on a widely used ‘growth model’ for assessing the impact of government size on economic growth. The findings indicate that small size of government contributes more on the economic growth of the countries. The results seem to be more robust by using fixed-effects model as compared to other static or even dynamic models.